(untitled) - Flockhart, Dan (San Francisco, 2007)
Fantasy sports are a hit worldwide, and now teachers and parents can take advantage of this phenomenon to give students a reason to look forward to doing math. The games and activities in Fantasy Basketball and Mathematics will get kids excited about learning and practicing math, even if they're not big sports fans. With this fun-filled educational resource, you can teach one math concept or many and plan lessons that can last for a week or a whole season.
Keywords: Sports,Mathematical recreations,Games in mathematics education,Thể thao,Toán,Trò chơi toán học; Mathematics,Toán học,Tiêu khiển